2011
DOI: 10.1097/hjh.0b013e32834068e0
|View full text |Cite
|
Sign up to set email alerts
|

Creatine kinase activity and blood pressure in a normal population: the Tromsø study

Abstract: Creatine kinase was associated with blood pressure in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
45
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 28 publications
(35 reference statements)
9
45
1
Order By: Relevance
“…This is in line with previous findings of CK as a main denominator of blood pressure 6,17,18 and reports of significant vasodilation of isolated resistance arteries after CK inhibition. 19 Furthermore, our data were collected in subjects of African and European ancestry and among the clinical spectrum of normotension to hypertension.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with previous findings of CK as a main denominator of blood pressure 6,17,18 and reports of significant vasodilation of isolated resistance arteries after CK inhibition. 19 Furthermore, our data were collected in subjects of African and European ancestry and among the clinical spectrum of normotension to hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…17,18 Furthermore, we reported that human isolated resistance artery contractility depends on CK and that specific CK inhibitors greatly attenuate human vascular contractility in vitro. 19 The explanation proposed for these findings was that in the absence of organ damage, high serum CK activity reflected high tissue CK activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, in that study, creatine kinase was not controlled for exercise, causing highly skewed data and a dilution of the association between creatine kinase and blood pressure [14,28]. Moreover, this study included only white individuals, and this population subgroup is known to have relatively low creatine and blood pressure levels, resulting in relatively small differences in blood pressure between treated controlled and treated uncontrolled patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this study included only white individuals, and this population subgroup is known to have relatively low creatine and blood pressure levels, resulting in relatively small differences in blood pressure between treated controlled and treated uncontrolled patients. Because of these differences, this post-hoc analysis was underpowered [14,28]. In our paper, we analyzed differences in resting creatine kinase between all blood pressure categories, as a primary outcome, with adequate sample size, and also adjusted for other predictors, including sex, age, glucose, ethnicity, and BMI, resulting in a clear association between creatine kinase and treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Non-fasting blood samples were analysed by standard methods at the Department of Laboratory Medicine, University Hospital of North Norway. Details on data collection have been described elsewhere for Tromsø 2, 3 and 4,13 Tromsø 514 and Tromsø 6 15. Because of summer vacation, no measurements were performed in July.…”
Section: Methodsmentioning
confidence: 99%